2004
DOI: 10.1073/pnas.0400835101
|View full text |Cite
|
Sign up to set email alerts
|

Akt plays a central role in sarcomagenesis induced by Kaposi's sarcoma herpesvirus-encoded G protein-coupled receptor

Abstract: We have recently engineered an in vivo endothelial cell-specific retroviral gene transfer system and found that a single Kaposi's sarcoma (KS)-associated herpesvirus͞human herpesvirus 8 gene encoding a G protein-coupled receptor (vGPCR), is sufficient to induce KS-like tumors in mice. By using this system, we show here that the Akt signaling pathway plays a central role in vGPCR oncogenesis. Indeed, a constitutively active Akt was sufficient to induce benign hemangiomas in mice, whereas heterozyogosity for PTE… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
133
0
1

Year Published

2008
2008
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 142 publications
(138 citation statements)
references
References 50 publications
4
133
0
1
Order By: Relevance
“…Consequently, the ORF45-induced RSK signaling becomes a crucial pathway involved in eIF4B phosphorylation during the viral lytic cycle (17). Interestingly, although ORF45 increased phosphorylation of both eIF4B and rpS6, we found that phosphorylation of eIF4B was not sensitive to rapamycin but that phosphorylation of rpS6 was, suggesting that eIF4B is phosphorylated by ORF45-activated RSK directly, whereas rpS6 is phosphorylated by mTOR/ S6K-dependent signaling that could be activated by RSK indirectly through phosphorylation of tuberous sclerosis protein 2 (55,58) or other KSHV gene products, such as viral G protein-coupled receptor or K1 (27)(28)(29)31). In any case, our data support the conclusion that the ORF45/RSK axis plays a crucial role in translational control during KSHV lytic replication through phosphorylation of eIF4B.…”
Section: Discussionmentioning
confidence: 66%
See 1 more Smart Citation
“…Consequently, the ORF45-induced RSK signaling becomes a crucial pathway involved in eIF4B phosphorylation during the viral lytic cycle (17). Interestingly, although ORF45 increased phosphorylation of both eIF4B and rpS6, we found that phosphorylation of eIF4B was not sensitive to rapamycin but that phosphorylation of rpS6 was, suggesting that eIF4B is phosphorylated by ORF45-activated RSK directly, whereas rpS6 is phosphorylated by mTOR/ S6K-dependent signaling that could be activated by RSK indirectly through phosphorylation of tuberous sclerosis protein 2 (55,58) or other KSHV gene products, such as viral G protein-coupled receptor or K1 (27)(28)(29)31). In any case, our data support the conclusion that the ORF45/RSK axis plays a crucial role in translational control during KSHV lytic replication through phosphorylation of eIF4B.…”
Section: Discussionmentioning
confidence: 66%
“…Kaposi sarcoma-associated herpesvirus (KSHV) is the etiological agent of endothelial neoplasm Kaposi sarcoma and two lymphoproliferative diseases, primary effusion lymphoma and multicentric Castleman disease. KSHV activates both MEK/ERK/RSK and AKT/mTOR/ S6K signaling pathways by multiple mechanisms (23)(24)(25)(26)(27)(28)(29)(30)(31)(32). We recently found that the immediate early and tegument protein open reading frame 45 (ORF45) of KSHV interacts with RSK1 and RSK2 and causes sustained activation of RSK and ERK during lytic replication (17).…”
mentioning
confidence: 99%
“…For example, drugs that inhibit the PI(3)K/Akt/mTOR (mammalian target of rapamycin) pathway hamper KS development and, in certain cases, induce tumor regression (Sodhi et al, 2004bStallone et al, 2005;Chaisuparat et al, 2008). Importantly, we show that the PI(3)K/Akt nexus is activated in human KS.…”
Section: Discussionmentioning
confidence: 68%
“…We recently showed that VEGF induces Rac activation through a Src/Vav2 signaling axis, whereas CXCR2 involves the PI(3)Kg pathway in the increase of endothelial permeability (Gavard and Gutkind, 2006;Gavard et al, 2009). In addition, Akt, a well known downstream target of PI(3)K signaling, has a prominent role in vGPCR sarcomagenesis (Sodhi et al, 2004b). To assess the potential involvement of PI(3)K, we first treated endothelial cells with the general PI(3)Kinase inhibitor wortmannin.…”
Section: Pi(3)mentioning
confidence: 99%
“…Indeed, macrophages have been reported to induce malignant progression in a breast cancer model by initiating the angiogenic switch [91] . Additionally, CXCL8-CXCR2 signaling facilitates migration and proliferation of endothelial cells [92] , and the AKT pathway is important for GPCR-dependent angiogenesis [93] following CXCR1 and CXCR2 activation [49,81] . Also, the human herpesvirus-8, an etiological agent of the highly vascular Kaposi's sarcoma, induces expression of CXCL8 [94] , providing further evidence for chemokine involvement in tumorigenesis [95] .…”
Section: Chemokines and Angiogenesismentioning
confidence: 99%